On The Move: Mobility in Perm’ Province, 1880-1914 - Rowson, Jonathan J. O. (2020)
This thesis examines mobility in provincial Russia in the late Imperial era (1880-1914). During this period, the Imperial state introduced new migration legislation which gave lower-class people increased opportunities to move for economic purposes. This thesis examines lower-class trajectories and temporalities in Perm’ Province, a region located on European Russia’s far periphery. It outlines the key socio-economic drivers for increased population and goods mobility at the turn of the twentieth century in the rural, industrial, and urban economies. Lower-class people were dynamic economic agents who made informed decisions to better their individual or household economies, adapting their trajectories and working practices to changing economic conditions, state policy, and new infrastructure developments. In doing so, this thesis contributes to the growing literature on population mobility, lower-class socio-economic agency and lived experiences, and the relations between periphery and metropole in late Imperial Russia.